Sevelamer carbonate in the treatment of hyperphosphatemia in patients with chronic kidney disease on hemodialysis - Vincenzo Savica; Domenico Santoro; Paolo Monardo; Agostino Mallamace; Guido Bellinghieri (Dove Medical Press, 2008)
Vincenzo Savica1,2, Domenico Santoro1, Paolo Monardo2, Agostino Mallamace1, Guido Bellinghieri11Experimental and Clinic Department of Internal Medicine and Pharmacology, University of Messina, Italy; 2Nephrology and Dialysis Unit, Papardo Hospital, Messina, ItalyAbstract: Sevelamer carbonate is an anion exchange pharmaceutical, developed to improve on the performance of the non-absorbable, non-calcium, and metal-free phosphate binder sevelamer hydrochloride. Sevelamer carbonate is expected not to worsen metabolic acidosis, as previously reported during long-term treatment with sevelamer hydrochloride in hemodialysis (HD) patients. Carbonate is the alternate counterion to chloride on the sevelamer polymeric backbone, but the active poly(allylamine) responsible for phosphate (PO4) binding remains unaltered. Therefore, sevelamer carbonate is expected to reduce elevated serum phosphorus level, similarly to sevelamer hydrochloride. Sevelamers are prescribed in uremic HD patients to control hyperphosphatemia, but the carbonate has also been proposed for the treatment of chronic kidney disease (CKD) non-dialysis patients. Although hyperphosphatemia is regarded as a main contributor to increased mortality in the HD population because of cardiovascular calcification, metabolic acidosis has also been advocated as a major player in the increased mortality in this population, by engendering malnutrition, negative nitrogen balance, and inflammation. This paper reviews the evidence showing that sevelamer carbonate is as good as sevelamer hydrochloride in terms of hyperphosphatemia control in CKD, but with a better outcome in serum bicarbonate balance.Keywords: chronic kidney disease, sevelamer carbonate, hyperphosphatemia, hemodialysis